The POKE Cikarang Community and the Dynamics of Life Partner Selection Among Christian Workers in the Midst of Diversity - Hutauruk, Rumani; Triposa, Reni; Boiliu, Esti Regina (PT FORMOSA CENDEKIA GLOBAL, 2025)
Marriage represents a crucial phase in human existence, encompassing not only personal dimensions but also reflecting values deeply rooted in faith, culture, and social obligations. This community service aimed to strengthen the faith-based fellowship of Christian workers within the POKE Cikarang community and to support their decision-making in selecting life partners amid workplace diversity. The program involved online and onsite mentoring, worship sessions, and small group discussions using contextual and participatory methods. Activities were conducted over six months through Zoom and WhatsApp platforms, enabling flexible engagement for participants. The results showed increased spiritual maturity, stronger interpersonal connections, and a more thoughtful approach to faith-based relationships. This initiative demonstrates that spiritual communities can foster unity, growth, and resilience in pluralistic professional environments.